2010
DOI: 10.1097/scs.0b013e3181d878e9
|View full text |Cite
|
Sign up to set email alerts
|

Application of Platelet-Rich Plasma in Maxillofacial Surgery

Abstract: The authors report their experience on 15 cases, including reconstructive surgery of the jaws, postextraction alveolar bone regeneration, and oral implantology. The aim of the study was to evaluate the different effects on jaws' bone regeneration with or without the use of local application of platelet-rich plasma (PRP). The results we report showed the efficacy of the PRP treatment: postoperative patients' satisfaction and low-morbidity course confirmed the quality of the results. The article will help the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 21 publications
1
52
0
Order By: Relevance
“…(2010) reported their experience on 15 cases, including reconstructive surgery of the jaw, post-extraction alveolar bone regeneration, and oral implantology. The results of their study revealed the efficacy of the PRP treatment in terms of post-operative patients' satisfaction and low-morbidity [63]. Anand et al .…”
Section: Methodsmentioning
confidence: 99%
“…(2010) reported their experience on 15 cases, including reconstructive surgery of the jaw, post-extraction alveolar bone regeneration, and oral implantology. The results of their study revealed the efficacy of the PRP treatment in terms of post-operative patients' satisfaction and low-morbidity [63]. Anand et al .…”
Section: Methodsmentioning
confidence: 99%
“…Histomorphological observations showed that 54% of patients treated with PRP achieved 100% bone regeneration within 24 weeks, compared with 38% of the control group. [36] This implies that there is acceleration of bone growth with PRP.…”
Section: Discussionmentioning
confidence: 99%
“…37, 38, 39 The potential of PRP in modulating soft- and hard-tissue formation and regeneration depends on the levels of released growth factors. 40 For peripheral nerve regeneration, as summarized in Table 2, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52 various known cytokines and growth factors within platelet-rich plasma, including transforming growth factor-β (TGF-β), platelet-derived growth factor, vascular endothelial growth factor, insulin-like growth factor and basic fibroblast growth factor (bFGF), have been discussed as being crucial for cell proliferation and differentiation, stimulation of angiogenesis and scar control in the process of regenerating peripheral nerve structures.…”
Section: Prp Treatment: Preparation and Biological Characteristicsmentioning
confidence: 99%